Juvenile Nasopharyngeal Angiofibroma, Experience of 35 Cases with Different Surgical Approaches (Medical Forum Monthly, 2024)
Objective: 1) To study the clinical presentation. 2) To study the outcome regarding recurrence, prognosis and complications of different surgical approaches of juvenile nasopharyngeal angiofibroma. Study design: Observational study. Place and duration of study: The study was conducted at department of Ear, Nose, Throat. Head & Neck Surgery, Quaid-e-Azam Medical College and Bahawal Victoria Hospital Bahawal Pur, from March 2005 to February 2009. Patients and methods: All young male patients presenting in ENT OPD/COD with complaint of recurrent nose bleeding, nasal obstruction and nasopharyngeal mass were admitted in ward. Detailed history was taken and thorough clinical examination done. Routine investigations and CT scan done in all cases. Staging done according to Fisch staging systems. Sufficient quantity of blood arranged and patient prepared for surgery. Specimen removed was sent for histopathological examination to confirm clinical diagnosis. Follow up was done for 12-18 months to see the recurrence and complications. Results: Total 35 young male patients clinically diagnosed as JNA and postoperatively confirmed by histopathology were included in the study. Age range was between 10-25 years, majority were between 12-20 years (n-31). All patients were male. All patients presented with epistaxis, nasal obstruction and nasopharyngeal mass. Other presenting symptoms were, anemia (n-29), nasal mass (n-27), ear blockage (n-27), nasal discharge (n-25), headache (n-22), snoring (n-15), speech defect (n-11) and proptosis (n-6). All patients under went surgery. Seventeen patients were approached through lateral rhinotomy, 12 through transpalatal approach and 06 through Weber Furguson approach. In 05 patients recurrence occurred and in 11 patients postoperative complications occurred. Conclusion: Meticulous surgical approach depending on the stage of JNA reduces the risk of recurrence and complications.